2015
DOI: 10.1186/s12989-015-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Cationic nanoparticles directly bind angiotensin-converting enzyme 2 and induce acute lung injury in mice

Abstract: BackgroundNanoparticles have become a key technology in multiple industries. However, there are growing reports of the toxicity of nanomaterials to humans. In particular, nanomaterials have been linked to lung diseases. The molecular mechanisms of nanoparticle toxicity are largely unexplored.MethodsAcute lung injury was induced in wild-type mice and angiotensin-coverting enzyme 2 (ACE2) knockout mice by the intratracheal instillation of cationic polyamidoamine dendrimer (PAMAM) nanoparticles. For rescue experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…We demonstrated that the ARB losartan could attenuate acute lung failure in a mouse model whose condition had been worsened after injection of the SARS-CoV-2 spike protein 9 . We also showed imbalanced RAAS in many predisposing conditions for ARDS, including sepsis, acid aspiration, bacteria, SARS-CoV-2, avian influenza (H5N1 and H7N9) infections, as well as nanoparticle aspiration 9 , 11 13 , 23 . These studies suggested that blocking the RAAS pathway and reducing angiotensin II levels could ameliorate lung injury 9 , 11 , 12 , 16 , 23 .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…We demonstrated that the ARB losartan could attenuate acute lung failure in a mouse model whose condition had been worsened after injection of the SARS-CoV-2 spike protein 9 . We also showed imbalanced RAAS in many predisposing conditions for ARDS, including sepsis, acid aspiration, bacteria, SARS-CoV-2, avian influenza (H5N1 and H7N9) infections, as well as nanoparticle aspiration 9 , 11 13 , 23 . These studies suggested that blocking the RAAS pathway and reducing angiotensin II levels could ameliorate lung injury 9 , 11 , 12 , 16 , 23 .…”
Section: Introductionmentioning
confidence: 76%
“…Although a wide variety of conditions, including SARS-CoV, sepsis, acid aspiration, bacteremia, and avian influenza (H5N1 and H7N9) infections, predispose patients to ARDS, a common mechanism seems to be an imbalance of RAAS 9 , 11 13 , 23 . Our previous studies in mice suggested that ACE, angiotensin II, and the type 1a angiotensin II receptor participate in disease pathogenesis, whereas ACE2 and the type 2a angiotensin II receptor could protect the mice from severe acute lung injury 9 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here also lend further support to the assertion that drug delivery systems cannot be considered as biologically inert and aside from their ability to improve drug delivery have additional, sometimes unexpected, biological and cellular effects [ 15 17 , 65 ]. Our study shows that in vivo modulation of the highly important EGFR cell signal transduction pathway can also be added to the growing list of intrinsic biological activities for PAMAM dendrimers that includes eliciting multiple gene expression changes in biological systems that may impact on siRNA activity and specificity [ 18 , 66 ], disrupting key platelet function [ 67 ], modulating Angiotensin-converting enzyme 2 activity [ 68 ] and exhibiting anti-inflammatory activity [ 20 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, phagocyte cells internalize spherical-shaped nanoparticles more easily than stretched-shaped structures ( 228 ). And although positively charged particles are taken up more avidly, negatively charged particles have been shown to exhibit lower toxicity ( 229 232 ). Nanoparticles can be made from different materials, metallic (e.g., silver, gold, and copper), magnetic (e.g., iron) (useful for imaging), ceramic, carbon-based, silica, lipid-based, or polymeric such as poly(amino acids), polysaccharides and poly(alpha-hydroxy acids).…”
Section: Targeting Immunological Activity Of Myeloid Cellsmentioning
confidence: 99%